Implementasi Manajemen Keuangan untuk Membangun Kebiasaan Menabung pada Anak TK di Tadika Tahfiz Nur Furqan,Malaysia - Ayu Dya Inayah; Syahrul Amsari (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Financial management is a very important life skill to have from an early age. Saving education is an important step in forming financial management skills, self-control and planning for the future in children. Educational activities carried out at Tadika Tahfiz Nur Furqan aim to improve children's understanding of the importance of implementing savings habits from an early age which will help them develop positive habits in managing finances. Qualitative descriptive methods were applied in this study through data collection techniques, namely observation, interviews, and documentation. The data obtained were analyzed to improve children's understanding of saving habits. The results of the study showed that children did not yet understand financial management and the application of saving, resulting in low interest in saving. However, this education succeeded in instilling positive habits and awareness of the importance of discipline in managing money. The practice of saving by making piggy banks from paper not only increases children's creativity but can also foster a sense of ownership and strengthen understanding about saving.